The effect of water on the solid state characteristics of pharmaceutical excipients: Molecular mechanisms, measurement techniques, and quality aspects of final dosage form - Szakonyi, Gergely; Zelkó, Romána (International Journal of Pharmaceutical Investigation)
In this paper we give an overview about the interaction of water molecules with pharmaceutical excipients. Most of these excipients are amorphous or partially amorphous polymers and their characteristics are very sensitive to the water content. In the course of the manufacturing processes water sorption is possible, therefore in some cases it is important to strictly control the residual moisture content of a dosage form. There are several mechanisms of water sorption, like water is able to bind to polar groups of hygroscopic excipients and could also exist in the capillary system of amorphous excipients. Several techniques are available to characterise the states of water inside the materials and the effects of residual water on polymers. For this purpose water sorption measurements, differential scanning calorimetry and the Fourier-transform infrared spectroscopy are reviewed. The importance of water content and storage conditions of pharmaceuticals on the properties of the final dosage forms are also demonstrated with practical examples.
Keywords: Differential scanning calorimetry; free volume; FT-IR spectroscopy; polymer; positron annihilation lifetime spectroscopy; water sorption